The effectiveness of reality therapy on functional flexibility and distress tolerance of married women - Houseinzadeh, zahra; Ghorbanshirodi, Shohreh; Khalatbari, javad; Rahmani, mohammad ali (Psychology of Woman Journal, 2021)
This research aimed to determine the effectiveness of reality therapy on behavioral flexibility and distress tolerance of married women. The present research was semi-experimental with pre-test and post-test with a control group and a 2-month follow-up; The sample was selected from 38 married women who referred to counseling centers in Tehran in 2018 who responded to the functional flexibility questionnaire of Connor and Davidson (2003) and distress tolerance of Simmons and Gaher (2005). Among them, 24 women were selected and randomly replaced in two reality therapy experimental groups (12 women) and the control group (12 women). The experimental group underwent Glasser's (2008) reality therapy intervention for eight 90-minute sessions, and the control group did not receive any intervention. Data were analyzed using repeated measures mixed analysis of variance. The results indicated the effect of reality therapy intervention on flexibility (F = 12.14, P = 0.004) and distress tolerance (F = 12.14, P = 0.004) and the stability of this effect in the follow-up phase. The research results suggest evidence that reality therapy intervention is a suitable method for improving and increasing functional flexibility and distress tolerance in married women.